2010
DOI: 10.1176/appi.ajp.2010.09071059
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Abilities and 50- and 100-msec Paired-Click Processes in Schizophrenia

Abstract: Objective Abnormal 50 and 100ms event-related brain activity derived from paired-click procedures are a well established finding in schizophrenia. There is little agreement on whether ratio score (second click/first click) paired-click group differences reflect an encoding or gating abnormality. In addition, the functional implications of the ratio score deficit remain unclear. In the present study, EEG and MEG were used to examine paired-click measures as well as the cognitive correlates of paired-click activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 59 publications
10
70
0
Order By: Relevance
“…Thoma et al (2003) discussed this observation in the context of the complexity of cognitive tasks and suggested that some cognitive functions successful performance requires enhanced sensory gating, whereas others are fostered by reduced gating. This may be compatible with a report by Smith et al (2010) showing significant correlations between gating and measures of attention but not with more complex cognitive domains e.g. working memory.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thoma et al (2003) discussed this observation in the context of the complexity of cognitive tasks and suggested that some cognitive functions successful performance requires enhanced sensory gating, whereas others are fostered by reduced gating. This may be compatible with a report by Smith et al (2010) showing significant correlations between gating and measures of attention but not with more complex cognitive domains e.g. working memory.…”
Section: Discussionsupporting
confidence: 92%
“…However, the opened sensory gating filter would imply a favourable individual cognitive performance which is not supported by all published investigations. Some authors published associations between stronger (better) P50 sensory gating and better performance on cognitive tasks in healthy subjects (Smith et al, 2010;Hsieh et al, 2004), while others observed no correlations with verbal learning, memory or neurophysiological markers of attention (Cullum et al, 1993;Boutros et al, 2004). Some reported the opposite relationship, worse P50 gating predicted better working memory performance and reduced reaction time in healthy subjects (Thoma et al, 2003) (Lijffijt et al, 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the current pattern of findings highlights the importance of the duration of exposure on sensory gating, and suggests the P50 difference score may be particularly sensitive to deficits in long-term cannabis users. P50 difference scores are arguably a more psychometrically reliable method than P50 ratio (Smith et al, 1994), however it is also possible that P50 ratio and difference scores may reflect slightly different neurobiological processes (Smith et al, 1994) suggests long-term exposure to cannabis may adversely affect encoding as well as well as gating (Smith et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These factors have led to the suggestion that the P50 could potentially serve as a useful biomarker for detecting disease presence and for assessing treatment response. Several studies have shown correlations between reduced P50 (gating and amplitude) and impaired performance on measures of sustained attention and speed of processing (Cullum et al, 1993, Erwin et al, 1998, Potter et al, 2006, Smith et al, 2010. Decreases in P50 gating and amplitude are related to reduced working memory performance in schizophrenia (Cullum et al, 1993, Smith et al, 2010.…”
Section: Mouse Correlates Of the Human Erp Waveformmentioning
confidence: 99%
“…Several studies have shown correlations between reduced P50 (gating and amplitude) and impaired performance on measures of sustained attention and speed of processing (Cullum et al, 1993, Erwin et al, 1998, Potter et al, 2006, Smith et al, 2010. Decreases in P50 gating and amplitude are related to reduced working memory performance in schizophrenia (Cullum et al, 1993, Smith et al, 2010. Furthermore, mice show a negative deflection in the ERP around 40 milliseconds that shares a remarkable similarity with the human N100.…”
Section: Mouse Correlates Of the Human Erp Waveformmentioning
confidence: 99%